KORBAN BULLYING DAN KONDISI PSIKOLOGIS SISWA MTS HASANAH PEKANBARU - Rini Wil Azmi; Zulfan Saam; Tri Umari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : Bullying among students shows an increasingly alarming rate every year. The forms of bullying that occur among students include physical, verbal, and psychological aspects. This study aims to determine the description of the form of bullying received by students and to know the description of the psychological condition of students bullying victims. Population in this research is all student of victim bullying class VIII which amounted to 133 students with sampling using total sampling technique. Data were collected using questionnaires with Likert scale and analyzed by quantitative method. The results of this study indicate that the victim of bullying is in a mild stage with the form of bullying received include bullying verbal, psychological and physical. The psychological condition of the victims of bullying is at an unfavorable level. When seen in his emotions, the form of emotion upset dominates rather than the other forms of emotion. Whereas when viewed on self-esteem, students of bullying victims have low self-esteem on the aspect of many people liked, the students do anything to be liked by friends. It is expected that this research can be useful and useful for everyone, especially for BK teachers and the school.Keywords : Victims of Bullying, Psychological Condition